GERMANRUSSIAN INSTITUTE OF ADVANCED TECHNOLOGIES: A PLATFORM FOR EDUCATION, RESEARCH AND INNOVATION - Alsu M. Gilmetdinova; Ekaterina V. Veselova (Высшее образование в России)
Abstract. The article describes the history, development and early achievements of the German-Russian Institute of Advanced Technologies (GRIAT), an international educational project aimed at offering double degree graduate programs in engineering fields. Despite being launched only two years ago, GRIAT is proud of its first MSc graduates who received the diploma of KNRTUBKAI and German partner university. Currently, there are over 130 students studying in 7 MSc programs. Over the last years, GRIAT has become a platform for developing research among German and Russian professors, a host for various international conferences, exhibitions and fairs as well as a peace-building bridge despite political turmoil. The ultimate goal of GRIAT is to become a fully functional German Institute in Russia to connect education, science and industry, to unite two nations and to become a pace-maker for science and innovation.